2020
DOI: 10.1101/2020.08.31.20184184
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

U.S. Food and Drug Administration utilization of postmarketing requirements and postmarketing commitments, 2009-2018

Abstract: Background/Aims: The U.S. Food and Drug Administration (FDA) outlines clinical studies as postmarketing requirements and commitments to be fulfilled following FDA approval of new drugs and biologics ("therapeutics"). As regulators have increasingly emphasized lifecycle evaluation of approved therapeutics, postmarketing studies are intended to advance our understanding of therapeutic safety and efficacy, yet little is known about how often clinical studies are outlined or the indications they investigate. To as… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Two investigators (JJS and JDW) identified all PMRs and PMCs outlined in the original approval letters available in the Drugs@FDA database. 14 , 15 , 16 …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Two investigators (JJS and JDW) identified all PMRs and PMCs outlined in the original approval letters available in the Drugs@FDA database. 14 , 15 , 16 …”
Section: Methodsmentioning
confidence: 99%
“…Two investigators (JJS and JDW) identified all PMRs and PMCs outlined in the original approval letters available in the Drugs@FDA database. [14][15][16] Among this sample of premarketing and postmarketing studies, we excluded studies that evaluated only the therapeutics' safety, pharmacokinetics and pharmacodynamics, bioavailability, dose escalation, or drug interactions (eTable 1 in the Supplement). Additionally, Phase 1 studies, extension studies, expanded access studies, and studies that included patients with a different indication or only healthy patients were excluded.…”
Section: Study Samplementioning
confidence: 99%
See 2 more Smart Citations